The Role of Targeted Social Media and Sales Promotion in Purchase Decision-Making: A Comprehensive Review - Nitin Kumar Jain; Simran Kesharwani, (Journal of Sales, Service and Marketing Research (e-ISSN: 2582-7804), 2025)
Social media and sales promotions have a significant influence on purchasing decisions in this digital age. It explores the process by which social media controls promotional operations, frequently dictating the strategies used by businesses, through an analysis of case studies and available data. We assess various paper presentations about social media marketing and sales promotion on buying decisions in this review. Numerous earlier studies come to the conclusion that social media has a significant role in consumer decisions. Higher awareness will therefore have a favourable impact on consumers' purchasing decisions. The review research also discusses how traditional and Instagram celebrities can affect consumers' decisions to buy. In the digital age, businesses can increase their efficacy in influencing purchase decisions and optimizing sales results by comprehending and effectively navigating social media's autocratic engagement.